2021
DOI: 10.1097/scs.0000000000007672
|View full text |Cite
|
Sign up to set email alerts
|

Using 3D Printing and Mirror Image Modeling in Orbital Floor Reconstruction

Abstract: Three-dimensional (3D) modeling and printing technologies are increasingly utilized as tools to assist in complex craniofacial reconstructions. Herein, the authors report the intraoperative use of sterilized 3D models printed in-house to mold a custom resorbable implant in the case of a pediatric patient with a unilateral complex orbital fracture. The imaging was processed with opensource software. Two patient-specific orbital models were 3Dprinted (Fig. 2): a life-size print of the patient's preoperative CT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…This included no randomized controlled trials or nonrandomized intervention trials but included 3 case series [20][21][22] and 4 case reports. [23][24][25][26] All articles were published between January 2017 and December 2022, and were available in English. The included studies are described in Supplemental Table 1, Supplemental Digital Content 1, http://links.lww.com/SCS/F800.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This included no randomized controlled trials or nonrandomized intervention trials but included 3 case series [20][21][22] and 4 case reports. [23][24][25][26] All articles were published between January 2017 and December 2022, and were available in English. The included studies are described in Supplemental Table 1, Supplemental Digital Content 1, http://links.lww.com/SCS/F800.…”
Section: Resultsmentioning
confidence: 99%
“…22 The individual case studies each described a patient with a frontoethmoidal meningoencephalocele, 23 a complex craniofacial cleft with hypertelorism, 24 an orbital fracture, 25 and a cranial intraosseous lipoma. 26 3DP was used in preoperative planning with the creation of mock surgical models in 2 studies, 23,24 used to create custom intraoperative cutting guides or molds in 6 studies, [20][21][22][24][25][26] and used to create custom cranioplasty implants in 2 studies. 24,26 The specific technology and materials used in the 3DP process were described in most of the included studies (Supplemental Table 2, Supplemental Digital Content 2, http://links.lww.com/ SCS/F801).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chai et al [51] published a pediatric case series wherein patient-specific 3D CT reconstruction models were used to help adapt the resorbable implant preoperatively, which reduced operative time. A case report by Akiki et al [52 ▪ ] similarly demonstrated the use of a 3D template to mold a resorbable implant to address an orbital floor and medial wall fracture in a pediatric patient. Although patient-specific implants (PSIs) have gained popularity in adult populations, their use in pediatrics is limited.…”
Section: Advancements In Reconstructive Techniquesmentioning
confidence: 99%
“…At the 18 months' follow-up, the authors reported no complications and normal eye projection. 16 Three-dimensionally printed PSIs and models have been shown to be anatomically accurate. Schön et al demonstrated that PSIs were accurate within a 1-mm range on postoperative CT scan.…”
Section: Advantages Of Psismentioning
confidence: 99%